2014
DOI: 10.2967/jnumed.114.143347
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG PET and Perfusion SPECT in the Diagnosis of Alzheimer and Lewy Body Dementias

Abstract: Brain imaging with glucose ( 18 F-FDG) PET or blood flow (hexamethylpropyleneamine oxime) SPECT is widely used for the differential diagnosis of dementia, though direct comparisons to clearly establish superiority of one method have not been undertaken. Methods: Subjects with Alzheimer disease (AD; n 5 38) and dementia with Lewy bodies (DLB; n 5 30) and controls (n 5 30) underwent 18 F-FDG PET and SPECT in balanced order. The main outcome measure was area under the curve (AUC) of receiver-operating-characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
125
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 173 publications
(146 citation statements)
references
References 28 publications
13
125
1
3
Order By: Relevance
“…Main results from the study have been reported elsewhere (O'Brien et al 2014). The study subjects were recruited prospectively from people aged over 60 with mild to moderate dementia (MMSE > 12) referred to clinical services in North-East England.…”
Section: Subjectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Main results from the study have been reported elsewhere (O'Brien et al 2014). The study subjects were recruited prospectively from people aged over 60 with mild to moderate dementia (MMSE > 12) referred to clinical services in North-East England.…”
Section: Subjectsmentioning
confidence: 99%
“…As described in more detail elsewhere, (O'Brien et al 2014) the PET scans were non-linearly spatially normalised to a study specific template. Scans were intensity normalised to the mean within a cerebellar region-of-interest (ROI) and smoothed with a 8 mm Gaussian.…”
Section: Spm Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…A recent comparison demonstrated that FDG-PET had superior sensitivity and specificity than HMPAO-SPECT in the diagnosis of dementia. 11 Both HMPAO-SPECT and FDG-PET involve the administration of an intravenous tracer, a waiting period prior to the scan, and lying still on a flat surface. The level of radioactivity received is similar in both tests and comparable to CT scans.…”
Section: Typical Imaging Findings In Dementia Subtypesmentioning
confidence: 99%
“…5 Amyloid deposition may be detected with PET using fluorine-18-labelled florbetapir, flutemetamol or florbetaben. Recently, PET has also been used to identify the presence of tau protein.…”
Section: Nuclear Medicine Brain Scans Can Be Useful In Atypical Dementiamentioning
confidence: 99%